Analysis of the Impact of Digital Transformation of the Legal Field on Data Cybersecurity - Fekolli, Saimir; Çela, Ervis; Erdolatov, Chynybek; Biyashev, Berik; Ismailova, Gulnoza (Law, State and Telecommunications Review, 2025)
[Purpose] To develop effective cybersecurity strategies in the context of digital transformation of the legal field. [Methodology/approach/design] The research methodology includes a comprehensive analysis of technological, organisational, and regulatory aspects of the problem. [Findings] The article examines international legal cybersecurity regulation and recommends approaches to adapt best practices. The human component in law firm cybersecurity is examined, and recommendations for boosting staff digital literacy are made. Quantum cryptography’s legal data protection potential and successful cyber-attacks on DLA are analysed. Piper, Cravath, Swaine & Moore, Jones Day. The introduction of cloud technologies in legal firms significantly increases the risk of unlawful access to confidential information. An examination of 2020–2023 cyberattacks on legal entities found a growing trend of automating hostile acts with AI. The vulnerability evaluation identifies crucial data protection issues in legal services digitisation. A model of an adaptive cyber security system that considers law firm business process transformation offers a significant reduction in attack likelihood. Rewriting the legislative framework for personal data protection in the context of digitalisation, including regulating blockchain technology in legal practice, is justified. The integration of digital platforms into legal activity introduces new cyber dangers that demand novel security. Examine the impact of lawyers’ remote work on corporate network security and offer ways to reduce hazards. [Practical implications] The results of the study form the basis for the development of effective cybersecurity strategies in the legal field and the improvement of relevant legislation, which is critical for ensuring the confidentiality and integrity of legal information in the digital age.